2010
DOI: 10.1016/j.jacc.2009.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Updated Meta-Analysis of Septal Alcohol Ablation Versus Myectomy for Hypertrophic Cardiomyopathy

Abstract: SA does seem to show promise in treatment of HOCM owing to similar mortality rates as well as functional status compared with SM; however, the caveat is increased conduction abnormalities and a higher post-intervention LVOTG. The choice of treatment strategy should be made after a thorough discussion of the procedures with the individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
131
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(145 citation statements)
references
References 35 publications
5
131
0
9
Order By: Relevance
“…However, we are still not sure whether this technique extends longevity of its target patients. Results from several studies suggest that ASA can extend longevity of patients with HCM [6][7][8][9][10][11][12]. Here, we extended evidence for this notion by directly comparing the survival of patients undergoing ASA vs. a group of conservatively treated patients with comparable pressure gradient and limiting symptoms.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, we are still not sure whether this technique extends longevity of its target patients. Results from several studies suggest that ASA can extend longevity of patients with HCM [6][7][8][9][10][11][12]. Here, we extended evidence for this notion by directly comparing the survival of patients undergoing ASA vs. a group of conservatively treated patients with comparable pressure gradient and limiting symptoms.…”
Section: Discussionmentioning
confidence: 64%
“…Studies have demonstrated that survival rates after ASA and myectomy in experienced centers were similar [6][7][8]. And, as survival after myectomy, survival after ASA is also comparable with that of general population [8,9].…”
Section: Introductionmentioning
confidence: 92%
“…Clinical outcomes are similar to those of myectomy, as shown in two recent meta-analyses, in which the only difference was the need for permanent pacing. 30,31 These results reflect the learning curve required for ASA, as was initially seen for myectomy, although not in recent publications.…”
Section: Comparison With Myectomymentioning
confidence: 55%
“…After the introduction of MCE, the outcome improved and complications were reduced [4,5]. Despite these techniques, gradient reduction after ASA remains slightly less compared with surgical myectomy [1,2]. This may be important since higher outflow gradients after ASA are associated with a less favourable long-term haemodynamic outcome [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, gradient reduction after ASA was slightly less favourable [1,2] and in a singlecentre study a higher rate of aborted sudden cardiac death was found [3]. The following case report illustrates the importance of coronary anatomy and infarction location in determining the outcome after ASA.…”
Section: Introductionmentioning
confidence: 94%